2021
DOI: 10.20944/preprints202105.0446.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interspecies Behavioral Variability of Medaka Fish Assessed by Comparative Phenomics

Abstract: Recently, medaka has been used as a model organism in various research fields. However, even though it possesses several advantages over zebrafish, fewer studies were done in medaka than zebrafish, especially its behaviour. Thus, to provide more information regarding its behaviour and to demonstrate the be-havioural differences between several species of medaka, we compared the behavioural performance and biomarker expression in the brain between four medaka fishes, which were Oryzias latipes, O. dancena, O. w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…We used the mirror test to assess zebrafish aggressiveness (Audira et al, 2021). The zebrafish were introduced to a rectangular tank (24.5 cm length × 14.5 cm height × 7.5 cm width) filled with 1.5 L of home tank water, with a mirror fixed to the vertical side wall.…”
Section: Methodsmentioning
confidence: 99%
“…We used the mirror test to assess zebrafish aggressiveness (Audira et al, 2021). The zebrafish were introduced to a rectangular tank (24.5 cm length × 14.5 cm height × 7.5 cm width) filled with 1.5 L of home tank water, with a mirror fixed to the vertical side wall.…”
Section: Methodsmentioning
confidence: 99%
“…Houle et al (2010) highlighted that limiting the number of phenotypic traits measured to those with some pre-established functional significance could obscure the identification of potentially important traits implicit in the biological response or endpoint of interest, and that high-dimensional phenotyping was necessary to identify the traits, or combinations of traits, that really matter. Now, phenomics is regularly utilised in characterising the genetic basis of complex traits, for tackling disease (Denny et al, 2010;Pendergrass et al, 2011;Hebbring, 2014;Özdemir, 2020), selective breeding (Crossa et al, 2021) and in the characterisation of responses to toxicants (Audira et al, 2020;2021;Hussain et al, 2020). Phenomics is also becoming increasingly utilised in the assessment of responses to environmental change, particularly within the crop sciences (e.g., Warringer et al, 2003;Schnaubelt et al, 2013;Singh et al, 2018;Adhikari et al, 2019;Li et al, 2019;Marsh et al, 2021;Tills et al, 2021;.…”
Section: What Is Phenomics?mentioning
confidence: 99%
“…While serotonin is synthesised from Trp in a whole range of species and performs important functions in many physiological processes, including mood in humans, 148 aggression in vervet monkey, 87 injurious behaviour in pigeon, hens and parrots 150 or catecholamines metabolism in rats, 149 surprisingly little comparative studies of serotonin pathway activity across species or strains thereof have been reported and these are mainly concerned with response of the pathway to manipulations, such as stress. 261 alterations in dietary Trp, 262 monoamine transporters in humans, rats and mice, 263 behavioural variability in Medaka fish strains 264 and mouse strain differences in serotonin-specific reuptake inhibitor sensitivity. 265 Table 6 summarises data published on species content of brain Trp and its 5-hydroxyindole metabolites 5-HT and Cichlid (6) All values are in µM.…”
Section: Species Differences In the Serotonin Pathwaymentioning
confidence: 99%